Design and simulation analysis of impact-resistant flexible drill pipe for rock-breaking rig. (November 2021) - Gao, Kangping; Xu, Xinxin; Shi, Ning; Jiao, Shengjie
In the process of drilling and coring by the rock-breaking rig, the drill rod is affected by the intermittent impact force, which reduces the efficiency of the rig to break the rock and increases the cost of the drilling and coring. Therefore, it is very important to improve the impact resistance of the drill pipe during the rock-breaking process. To achieve this goal, a flexible design of the drill pipe was carried out, and a dynamical model of the drilling rig based on a series elastic actuator was established. Considering the dynamic performance of the system, a torque feedforward link is introduced and a control model based on the force source is established. The influence of the equivalent inertia of the transmission system and the series elastic actuator damping coefficient on the system stability was analyzed by drawing the frequency domain characteristic curve of the system. By using the control and Simulink simulation software, the electromechanical simulation of the model is carried out, and the torque step tracking response of the system is obtained. A torque feedforward link is introduced to establish the control model of the system based on force source. Through dynamic simulation software ADAMS, dynamic and static impact simulation experiments were carried out on the system. The results show that when a force of 200 N is applied to the output end of the drill pipe in the tangential direction, the maximum moments received by the joint under static and dynamic environments are 34.1 N·m and 57.9 N·m, respectively. When the impact force disappears, the time required for the flexible drill pipe to reach a stable state is only 0.15 s, which verifies that the series elastic actuator–based drill pipe model can alleviate the impact of the external environment and protect the internal structure of the rig.